Identification, characterization and full-length sequence analysis of a novel endornavirus in common sunflower (Helianthus annuus L.) - Wen-wen LIU; Min XIN; Meng-ji CAO; Meng QIN; Hui LIU; Shou-qi ZHAO; Xi-feng WANG (Journal of Integrative Agriculture, 2018)
To identify the possible quarantine viruses in seven common sunflower varieties imported from the United States of America and the Netherlands, we tested total RNAs extracted from the leaf tissues using next-generation sequencing of small RNAs. After analysis of small RNA sequencing data, no any quarantine virus was found, but a double-stranded RNA (dsRNA) molecule showing typical genomic features of endornavirus was detected in two varieties, X3939 and SH1108. Full-length sequence and phylogenetic analysis showed that it is a novel endornavirus, temporarily named as Helianthus annuus alphaendornavirus (HaEV). Its full genome corresponds to a 14 662-bp dsRNA segment, including a 21-nt 5' untranslated region (UTR), 3' UTR ending with the unique sequence CCCCCCCC and lacking a poly(A) tail. An open reading frame (ORF) that encodes a deduced 4 867 amino acids (aa) polyprotein with three domains: RdRP, Hel and UGT (UDP-glycosyltransferase). HaEV mainly distributed in the cytoplasm but less in the nucleus of leaf cells by fluorescence in situ hybridization (FISH) experiment. This virus has a high seed infection rate in the five varieties, X3907, X3939, A231, SH1108 and SR1320. To our knowledge, this is the first report about the virus of the family Endornaviridae in the common sunflower.